Assessing the Influence of Strategic Leadership on the Operational Performance, Public Trust, and Accountability of Law Enforcement Agencies in South Sudan - Ekidor, Paul Ekal; Wekesa, Peter Wafula; Kiprono, Wilson (Human Resource and Leadership Journal, 2025)
Purpose: The purpose of the study was to critically examine the influence of strategic leadership on the operational performance, public trust, and accountability of law enforcement agencies in South Sudan, with particular attention to the South Sudan National Police Service (SSNPS) and the Criminal Investigation Department (CID). Methodology: The research was conducted using a qualitative case study design involving 30 purposively selected respondents from law enforcement institutions, civil society organizations, reform agencies, and community leadership in Juba and selected state capitals. Data was collected through semi-structured interviews, focus group discussions, and document analysis, and analyzed thematically using NVivo software. Findings: The study reveal that the absence of strategic leadership has led to fragmented operations, weak community engagement, and limited internal accountability. However, isolated examples of visionary leadership within specific police units suggest that transformational and strategic leadership can significantly improve service delivery, rebuild public trust, and promote institutional legitimacy. Unique Contribution to Theory, Policy and Practice: The study concludes that leadership is not a peripheral concern but a central pillar of law enforcement reform in fragile states. It recommends the institutionalization of leadership development programs, empowerment of oversight bodies, and alignment of police reform efforts with national development goals. The study offers practical insights for policymakers, development partners, and reform practitioners seeking to advance democratic policing and institutional resilience in South Sudan and similar contexts.